How "critical" are the critical success factors (CSFs)?: Examining the role of CSFs for ERP. Issue 1 (28th January 2014) - Ram, Jiwat; Corkindale, David
Abstract : Purpose: – The authors aim to examine the literature on enterprise resource planning (ERP) to establish whether the critical success factors (CSFs) for achieving stages of an ERP project have been empirically shown to be "critical". Design/methodology/approach: – The authors used a systematic approach to review 627 refereed papers published between 1998 and 2010 on ERP, from which 236 papers related to CSFs on ERP were selected for analysis. The authors employed procedures from qualitative and interpretive research methods, to analyse and interpret the material using five-step procedure of gathering, categorising, coding, analysing and comparing the data. Findings: – Prior studies have identified a large number of CSFs for ERP implementation success or improved performance outcomes. The authors have shown that a limited number of CSFs have been empirically investigated for their role in, and effect on, implementation success or post-implementation performance outcomes. While reporting the factors that have some evidence to support them, the authors question the utility of the general concept of CSFs. Research limitations/implications: – The authors' findings question the validity of many of the claimed CSFs and the utility of the general body of literature on CSFs. The authors caution researchers who may plan to use claimed CSFs for ERP in their research to carefully examine the veracity of the claim before proceeding. Practical implications: – The findings can help managers to focus their attention, priorities, resources and leadership on managing the CSFs that have been established to be critical for achieving ERP project implementation and/or performance outcomes. Originality/value: – The results provide new insights into the usefulness of CSFs and indicate that merely identifying possible CSFs is not sufficient to help with ERP success. Further investigation is required to establish the criticalness of the proposed CSFs before managerial time is devoted to them.